Application of the interval-training method for the development of aerobic work capacity in footballers (case of U20) - Bensalem, Salem (sports creativity, 2025)
Application of the interval training method for developing the aerobic and anaerobic work capacity of footballers (U20 case). Objective: The primary objective of this research is to study the development of the aerobic and anaerobic physical work capacity of Algerian footballers using the interval training method. Methods and results: As part of the experiment, 24 U-20 players from ABS (Amel de Bou-saada) underwent four educational tests related to the energy systems most used in football: the 12-minute Cooper test, 400 meters, 30-meter sprint, and five multi-jump tests. The results of the experimental group showed significant improvement compared to those of the control group, with a highly significant difference (p < 0.001) and marked progress in all tests. Conclusion – Interval training proves effective in developing the aerobic and anaerobic capacities of athletes; it is suitable